Evaluation of redox-sensitive metals in marine surface sediments influenced by the oxygen minimum zone of the Humboldt Current System, Northern Chile - Castillo, Alexis; Valdes, Jorge; Sifeddine, Abdel; Vega, Sue-Ellen; Diaz Ochoa, Javier Augusto; Marambio, Yery (My University, 2019)
Upwelling coastal systems can be used to understand how dissolved oxygen and biological productivity control the accumulation of redox-sensitive metals in marine sediments. The aluminium (Al), cadmium (Cd), iron (Fe), nickel (Ni), molybdenum (Mo), vanadium (V), total organic carbon (TOC), total nitrogen (TN) and total sulfur (TS) contents in surficial sediment collected from different water depths (30, 70, and 120 m) in three northern Chilean bays influenced by coastal upwelling and oxygen minimum zones (OMZs) were measured. Principal component analysis (PCA), cluster analysis, and Spearman's rank correlation were used to identify the mechanisms responsible for the redox-sensitive metal accumulation. The content of redox-sensitive metals and organic components in sediment increased with increasing water column depth, whereas lithogenic metals decreased. In the Mejillones del Sur and Caldera bays, the enrichment factors of the redox-sensitive metals showed enrichment for all metals with depth. The Cd and V enrichments are mainly the product of biogenic flow to the seabed, and the Mo and Ni enrichments are due to preservation under low subsurface oxygen conditions. Sulfate reduction is not an important mechanism in the accumulation of redox-sensitive metals in the sediment of the three bays. The PCA showed that the behaviors of the redox-sensitive metals and organic components reflect differences in the effects of the OMZ in sediment along the coast of northern Chile, with a more intense OMZ in Mejillones del Sur bay and weaker OMZs in Caldera and Inglesa bays. However, the high degree of enrichment in redox-sensitive metals in Caldera Bay can be attributed to the intense activity of the mining industry near the bay, a situation that produces geochemical behavior similar to that observed in Mejillones del Sur Bay. (C) 2018 International Research and Training Centre on Erosion and Sedimentation/the World Association for Sedimentation and Erosion Research. Published by Elsevier B.V. All rights reserved.
Keywords: redox sensitive-metals; atacama desert; enrichment factor; mejillones del sur bay; caldera bay system; pca